"I'm trying to save some lives here!": Critical dramatic inquiry in the aftermath of Hurricane Katrina. Issue 3 (5th December 2016) - Enciso, Patricia; Edmiston, Brian; Volz, Allison; Lee, Bridget; Sivashankar, Nithya
Abstract : Purpose: The purpose of this paper is to illustrate the plans for and implementation of critical dramatic inquiry with middle school youth. The authors also provide a theoretical frame for understanding dramatic inquiry as an embodied, persuasive and reflexive practice that can inform and transform the ways youth and their teachers experience their own and others' worlds. Throughout, the authors argue for the centrality of imagination in youth literacies and critical inquiry. Design/methodology/approach: Working with Stetsenko's (2008) concepts of contribution and agency, the authors considered the different ways youth "found [their] place among other people and ultimately, [found] a way to contribute to the continuous flow of sociocultural practices" (p. 17). Further, the authors considered Stetsenko's (2012) reference to moral philosophy and the idea that "humans are understood as being connected with the world precisely through their own acts – through what has been termed "engaged agency" in moral philosophy (Taylor, 1995, p. 7)". The authors read and annotated documents, noting key moments in the videos where youth collaborated in "finding a place among other people" and became "connected with the world […] through their own acts". Findings: The authors identified three ways dramatic inquiry orients youth in time-space, offering addresses and possibilities for answerability that direct their actions toward critical, ethical questions: creating a life through embodied positioning, reflecting on action through transformation of representations and establishing a direction for one's own becoming through persuasion and answerability. These three modes of contributing to a dramatic inquiry extend current research and thought about drama by pointing to specific contributions to and purposes for action in drama experiences. Research limitations/implications: This work represents a single two-session workshop of teacher research with middle school youth engaged in dramatic inquiry, and is, therefore, the beginning of a conceptual framework for understanding dramatic inquiry as critical sociocultural practice. As such, this work will need to be developed with the aim of extending the dramatic inquiry work across several days or weeks, to trace youth insights and subsequent actions. Practical implications: Critical literacy educators who want to implement dramatic inquiry will find clear descriptions of practices and an analytic framework that supports planning for and reflection on social change arts-based experiences with youth. Social implications: The authors argue that educators who aim to support youth actions, in relation to multiple viewpoints and possible futures, need to pose imagined and dramatized addresses to which youth can imagine and embody possibilities and express possible answers (Bakhtin). Based on Stetsenko's transformative activist stance, the authors argue that drama-based experiences disrupt the everyday so youth may collectively explore and contribute to an emerging vision of equity and belonging. Originality/value: Few studies have engaged Stetsenko's transformative activist stance as a way to understand learning, social change and the role of imagination. This study describes and explores a unique instantiation of process drama informed by critical sociocultural theory.